Classroom Teachers as Learning Leaders in Fostering Higher Order Thinking Skills through Civics Education in Elementary Schools - Amberansyah, Amberansyah; Harsono, Arta Mulya Budi; Nafisah, Ainun (Paedagoria : Jurnal Kajian, Penelitian dan Pengembangan Kependidikan, 2026)
This study aims to describe the role of a classroom teacher as a leader in the learning process who is able to develop higher-order thinking skills (HOTS) through civic education subjects in elementary schools located in wetland environments. This study uses a qualitative method with a single case study approach, conducted at SDN Sungai Telan Besar 2, Barito Kuala Regency, focusing on a fifth-grade teacher. Data were collected through observation, in-depth interviews, focus group discussions, and a study of various documents. The data were then analyzed using an interactive model developed by Miles & Huberman. The results showed that the teacher was able to design HOTS-based learning, integrate local phenomena such as tidal flooding and the cultural value of Kayuh Baimbai, and lead class discussions democratically by applying Socratic questioning and Problem-Based Learning strategies. In addition, the teacher also encouraged students to think critically through reflection and a culture of questioning. The teacher also played a transformative role by influencing colleagues and involving parents and the community. These findings indicate that contextual, innovative, and adaptive teacher leadership is crucial in developing higher-order thinking skills and shaping student character in areas with special geographical conditions, such as wetlands.